Development of an active and passive finger rehabilitation robot using pneumatic muscle and magnetorheological damper. (May 2020) - Wang, Daoming; Wang, Yakun; Zi, Bin; Cao, Zixiang; Ding, Huafeng
Highlights: An FRR is developed for active and passive training using two PMs and an MR damper. An underactuated mechanism is proposed for independent training of all finger joints. Modelling of kinematics, statics and dynamics of the FRR is presented. The motion and force properties of the FRR are experimentally evaluated. Abstract: This paper presents the development of a finger rehabilitation robot (FRR) for active and passive training to fulfill the requirements of different rehabilitation stages. In the design, an antagonistic pair of pneumatic muscles (PMs) are utilized to exert a bidirectional force for passive training, and a controllable magnetorheological (MR) damper is used to provide a damping force for active training. In this paper, first, a detailed illustration of the mechanical design of the FRR, including the driving, transmission and actuating mechanisms, and the damping device, is presented. Subsequently, the kinematic analysis and simulation are described, followed by the static and dynamic analysis of the designed FRR. This paper details the static force transfer of the transmission mechanism, and the establishment of dynamic equations for the passive training system. Finally, an experimental set-up is established, and several passive and active training experiments are conducted for the performance evaluation of the FRR prototype. The results validate the feasibility and stability of the developed FRR.